Optimised tool for the evaluation of the Smart City Index - Correia, Diogo Miguel Mendes (2018)
Cities are becoming overcrowded, therefore city administrations have to adopt measures to improve city processes and living conditions. The purpose of the present work is to find a tool which cities throughout the globe can use to measure its Smart City level and identifying areas of action in terms of urban planning and the politics they shall promote. Unlike other indexes, this tool have into consideration citizen’s opinion, because a Smart City shall be the city which promotes the better quality of life for its citizens. Through an inquiry, citizens are asked to evaluate and prioritize the different KPIs and Sub Dimensions, having these data been based on different sources of information (literature, state of the art of observed real facts and benchmarking work). The results have contributed to the calculation of the different coefficients and after that as inputs for the formulation of the equation that will define the Smart City index of a city.